Experience with the use of undenatured type II collagen in patients with stage III knee osteoarthritis: a multicenter, prospective, double-blind, placebo-controlled, randomized trial - Liudmila I. Alekseeva; Natalia G. Kashevarova; Elena A. Taskina; Ekaterina A. Strebkova; Tatiana A. Korotkova; Evgenia P. Sharapova; Natalya M. Savushkina; Aleksander M. Lila; Nadezhda A. Shostak; Irina I. Nesterovich; Viktoriia A. Dedkova; Vasiliy B. Vasilyuk; et al. (Терапевтический архив)
Introduction. Current strategies for treating osteoarthritis (OA) are based on a multimodal approach that includes pharmacological and non-pharmacological methods. Undenatured chicken collagen type II (NK2) is considered safe and effective for maintaining joint health and can be used alone and combined with drugs for OA treatment.